Urząd do spraw Wyznań a kwestia własności kościelnych majątków poniemieckich na Ziemiach Zachodnich i Północnych: Office for Religious Affairs and the ownership of former German church estates in the Western and Northern territories - Krawczyk, Michał (Management and Administration Journal, 2021)
The article analyzes the historical and legal dispute between the communist authorities and the Church, concerning the ownership of former German church estates situated in the Western and Northern territories. The dispute, for over a decade, put a shadow on the mutual relations between the state and the Church.